Contemporary museum architecture and design : theory and practice of place - Lindsay, Georgia (New York, NY : Routledge, 2020)
"Contemporary Museum Architecture and Design showcases eighteen diverse essays written by people who design, work in, and study museums, offering a variety of perspectives on this complex building type. Throughout, the authors emphasize new kinds of experiences that museum architecture helps create, connecting ideas about design at various levels of analysis, from thinking about how the building sits in the city to exploring the details of technology. With sections focusing on museums as architectural icons, community engagement through design, the role of gallery spaces in the experience of museums, disability experiences, and sustainable design for museums, the collected chapters cover topics both familiar and fresh to those interested in museum architecture. Featuring over 150 color illustrations, this book celebrates successful museum architecture whilst the critical analysis sheds light on important issues to consider in museum design. Written by an international range of museum administrators, architects, and researchers this collection is an essential resource for understanding the social impacts of museum architecture and design for professionals, students, and museum-lovers alike"--
OCLC-licensed vendor bibliographic record.
Keywords: Museum architecture; ARCHITECTURE / General